Clinical outcomes by baseline metastases in patients with renal cell carcinoma treated with lenvatinib plus pembrolizumab versus sunitinib: Post hoc analysis of the CLEAR trial - Grünwald, Viktor; McKay, Rana R; Buchler, Tomas; Eto, Masatoshi; Park, Se Hoon; Takagi, Toshio; Zanetta, Sylvie; Keizman, Daniel; Suárez, Cristina; Négrier, Sylvie; Lee, Jae Lyun; Santini, Daniele; et al. (International journal of cancer, 2025)
Lenvatinib plus pembrolizumab significantly improved efficacy versus sunitinib in treatment of advanced renal cell carcinoma (aRCC) in the phase 3 CLEAR study. We report results of an exploratory post hoc analysis of tumor response data based on baseline metastatic characteristics of patients who received lenvatinib plus pembrolizumab versus sunitinib, at the final overall survival analysis time point of CLEAR (cutoff: July 31, 2022). Treatment-naïve adults with aRCC were randomized to: lenvatinib (20 mg PO QD in 21-day cycles) plus pembrolizumab (n = 355; 200 mg IV Q3W); lenvatinib plus everolimus (not reported here); or sunitinib (n = 357; 50 mg PO QD; 4 weeks on/2 weeks off). The most common (lenvatinib plus pembrolizumab; sunitinib, respectively) metastatic site was lung (71.0%; 63.9%), followed by lymph node (45.6%; 43.7%), bone (22.5%; 24.9%), and liver (17.7%; 19.6%). Across treatment arms, ≥65% had two or more metastatic organs/sites involved, >80% of patients had nontarget lesions, and ~45% had baseline sums of diameters of target lesions ≥60 mm. Lenvatinib plus pembrolizumab demonstrated greater progression-free survival, objective response rate, and duration of response versus sunitinib across evaluable subgroups regardless of site or size of baseline metastasis or number of metastatic sites at baseline. Overall survival generally trended to favor lenvatinib plus pembrolizumab versus sunitinib; and tumor shrinkage was greater across sites (lung, lymph node, liver, and bone) for patients in the lenvatinib-plus-pembrolizumab arm versus the sunitinib arm. These results further support lenvatinib plus pembrolizumab as a standard-of-care in patients with aRCC regardless of site or size of baseline metastasis or the number of metastatic sites.
Keywords: fenylmočovinové sloučeniny; výsledek terapie; Sunitinib; nádory ledvin; Neoplasm Metastasis; Male; chinoliny; Antineoplastic Combined Chemotherapy Protocols; karcinom z renálních buněk; Kidney Neoplasms; Adult; Aged; dospělí; mužské pohlaví; senioři; Phenylurea Compounds; sunitinib; humanizované monoklonální protilátky; Antibodies, Monoclonal, Humanized; Treatment Outcome; senioři nad 80 let; lidé; ženské pohlaví; Humans; protokoly protinádorové kombinované chemoterapie; Aged, 80 and over; Carcinoma, Renal Cell; Quinolines; Female; metastázy nádorů; lidé středního věku; Middle Aged